COMPARATIVE ANALYSIS OF ON-GRID AND OFF-GRID SOLAR PANEL INSTALLATIONS IN A BUILDING WITH A REQUIREMENT OF 60.5 KWp - Fachruroji; Wahyudi, Muhammad Firman; Mubarok, Rizky; Munawar, Aris (Journal of Electronic and Electrical Power Applications, 2024)
Along with the increasing use of electrical energy and air pollution, one of which is caused by fossil fuel resources, has encouraged an increase in the use of renewable energy, especially solar power. Solar Power Plants (PLTS) have become an attractive alternative, especially for industrial and residential needs because they can reduce the cost of conventional electricity bills. At the design stage of the Solar Power Plant on-grid and off-grid systems in buildings with a power of 60,500 Wp by going through the stages of calculating the required load according to the conditions in the building, to obtain the required PLTS component capacity. In the long term, there will be an understanding of the use of renewable energy sustainably. The comparison results show that the cost between installing on-grid PLTS and installing off-grid PLTS is actually greater for on-grid PLTS with a cost of Rp. 444,301,500 than for installing off-grid PLTS with a cost of Rp. 332,214,000. However, the on-grid PLTS system offers a better system because it does not require a large area for battery storage, lower maintenance costs and can remain connected to the main network so it is very suitable for industrial needs.